Structural and Biochemical Characterization of Thioredoxin-2 from Deinococcus radiodurans - Min-Kyu Kim; Lei Zhao; Soyoung Jeong; Jing Zhang; Jong-Hyun Jung; Ho Seong Seo; Jong-il Choi; Sangyong Lim (Antioxidants, 2021)
Thioredoxin (Trx), a ubiquitous protein showing disulfide reductase activity, plays critical roles in cellular redox control and oxidative stress response. Trx is a member of the Trx system, comprising Trx, Trx reductase (TrxR), and a cognate reductant (generally reduced nicotinamide adenine dinucleotide phosphate, NADPH). Bacterial Trx1 contains only the Trx-fold domain, in which the active site CXXC motif that is critical for the disulfide reduction activity is located. Bacterial Trx2 contains an N-terminal extension, which forms a zinc-finger domain, including two additional CXXC motifs. The multi-stress resistant bacterium Deinococcus radiodurans encodes both Trx1 (DrTrx1) and Trx2 (DrTrx2), which act as members of the enzymatic antioxidant systems. In this study, we constructed Δdrtrx1 and Δdrtrx2 mutants and examined their survival rates under H2O2 treated conditions. Both drtrx1 and drtrx2 genes were induced following H2O2 treatment, and the Δdrtrx1 and Δdrtrx2 mutants showed a decrease in resistance toward H2O2, compared to the wild-type. Native DrTrx1 and DrTrx2 clearly displayed insulin and DTNB reduction activity, whereas mutant DrTrx1 and DrTrx2, which harbors the substitution of conserved cysteine to serine in its active site CXXC motif, showed almost no reduction activity. Mutations in the zinc binding cysteines did not fully eliminate the reduction activities of DrTrx2. Furthermore, we solved the crystal structure of full-length DrTrx2 at 1.96 Å resolution. The N-terminal zinc-finger domain of Trx2 is thought to be involved in Trx-target interaction and, from our DrTrx2 structure, the orientation of the zinc-finger domain of DrTrx2 and its interdomain interaction, between the Trx-fold domain and the zinc-finger domain, is clearly distinguished from those of the other Trx2 structures.